Giải pt $\frac{6x}{x²-x-6}$+$\frac{x}{3-x}$= $\frac{2}{x+2}$-1

Question

Giải pt
$\frac{6x}{x²-x-6}$+$\frac{x}{3-x}$= $\frac{2}{x+2}$-1

in progress 0
Maria 1 năm 2021-08-22T22:08:50+00:00 2 Answers 22 views 0

Answers ( )

    0
    2021-08-22T22:09:53+00:00

    Đáp án: `S={0}`

     

    Giải thích các bước giải:

         `frac{6x}{x²-x-6} +\frac{x}{3-x} =\frac{2}{x+2}-1`

    ĐK: $\begin{cases} x≠-2 \\x≠3 \end{cases} $

    `<=>  frac{6x}{x²-x-6} +\frac{x}{3-x} -\frac{2}{x+2}=-1`

    `<=> \frac{6x}{(x+2)(x-3)} -\frac{x}{x-3} -\frac{2}{x+2}=-1`

    `<=> \frac{6x -x(x+2) -2(x-3)}{(x+2)(x-3)}=-1`

    `<=> 6x-x² -2x -2x +6=-(x+2)(x-3)`

    `<=> -x² +2x +6=-x² +3x -2x +6`

    `<=> 2x =x`

    `<=> 2x-x=0`

    `<=> x=0` (TM)

    Vậy `S={0}`

     

    0
    2021-08-22T22:10:31+00:00

    `(6x)/(x^2-x-6)+x/(3-x)=2/(x+2)-1`     `Đkxđ:x\ne3,x\ne-2`

    `⇔(6x)/((x^2-3x)+(2x-6))-x/(x-3)=(2-x-2)/(x+2)`

    `⇔(6x)/((x-3)(x+2))-(x(x+2))/((x-3)(x+2))=(-x(x-3))/((x-3)(x+2))`

    `⇒6x-x^2-2x=-x^2+3x`

    `⇔6x-2x-3x=0`

    `⇔x=0` `(tm` `đkxđ)`

    Vậy tập nghiệm của phương trình là: `S={0}`.

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )